2018
DOI: 10.22159/ajpcr.2017.v11i1.21251
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Toxicological Studies of Ricinodendron Heudelotii (Baill.)

Abstract: Objective: This work assessed the antimicrobial activity and toxicological consequence of the ethanolic extract of Ricinodendron heudelotii (Baill). Methods:The antimicrobial potential of the leaf extract was investigated against 9 different microorganisms using the agar well diffusion method while the minimum inhibitory concentration (MIC) was ascertained. Toxicity evaluations were carried out on five groups of seven albino rats each for 28 days. Rats in Group A received normal saline, while those in Groups B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The qualitative phytochemical screening of the butanol and ethylacetate fractions of R. heudelotii revealed the presence of tannins, flavonoids amongst others as reported by Yakubu et al. [8]. This might account for the antiinflammatory potential of these two fractions.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The qualitative phytochemical screening of the butanol and ethylacetate fractions of R. heudelotii revealed the presence of tannins, flavonoids amongst others as reported by Yakubu et al. [8]. This might account for the antiinflammatory potential of these two fractions.…”
Section: Discussionmentioning
confidence: 60%
“…The bark helps cure malaria, yellow fever, and dysentery and equally has diuretic functions [7]. Recently, we reported the antimicrobial effect of R. heudelotii extract [8] and the cytotoxic effect of isolated compounds from the leaf extract [9]. It was also reported that the leaf extract exhibited regulatory role on the toxicity of artemisinin when co-administered with artemisinin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study of Oyono et al, (2014) has reported that, crude bark methanolic extract was active on 8 of 12 strains tested, with MIC ranging from 188 to 750 µg/ml and MBC from 375 to 1500 µg/ml, having diameters of inhibition zones from 12 to 19.67 mm. Similarly, the ethanolic leaves extract revealed the inhibition zone and minimum inhibitory concentration (MIC) ranging from 18 to 36 mm and 31.25 to 62.5 mg/mL, respectively against seven microorganisms: Pseudomonas aureginosa, Shigella sp., Escherichia coli (Gram-negatives), Staphylococcus aureus, Bacillus sp., Micrococcus sp., Streptococcus faecalis (Yakubu et al, 2018). This ethanolic leaf extract as well as the work of Oyono et al, (2014) on the methanolic bark extract showed no inhibition against following microorganisms: Klebsiella pneumoniae, Candida albicans, and Salmonella sp.…”
Section: Ricinodendron Heudelotiimentioning
confidence: 57%
“…It is known that plants containing phenolic compounds, flavonoids and tanins possess antioxidant and anti-inflammatory properties (Yakubu et al, 2018).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…belongs to the Euphorbiaceae family, whose species possess an array of medicinal effects. In traditional medicine, Ricinodendron heudelotii is used in the treatment of anemia, stomachache, cough, fever, dysentery, malaria, infertility, and antidiuretic [ 10 12 ]. In West Cameroon, the folk medical practice considers the stem bark of R. heudelotii as a useful remedy against cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%